2007
DOI: 10.1039/b618898b
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of methanol to dimethoxymethane under mild conditions over V2O5/TiO2 with enhanced surface acidity

Abstract: Dimethoxymethane was synthesized from the direct oxidation of methanol with high conversion and selectivity over specially designed bifunctional V(2)O(5)/TiO2 catalysts with redox and enhanced acidic character, in which the surface acidity played an essential role for inhibiting the formation of formaldehyde through the enhanced condensation reaction of formaldehyde with methanol to produce dimethoxymethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…For instance, unsupported and silica-supported crystallites of vanadium pentoxide show high selectivity towards formaldehyde with the yield of 96-98 % in the temperature range of 300-400 °С [5][6][7][8]. In contrast, monolayer V 2 O 5 /TiO 2 catalysts demonstrate high activity and selectivity in the methanol oxidation to methyl formate and to dimethoxymethane at low temperatures (100-200 °С), whereas the formation of formaldehyde is greatly suppressed [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. On the other hand, all products mentioned above are of practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, unsupported and silica-supported crystallites of vanadium pentoxide show high selectivity towards formaldehyde with the yield of 96-98 % in the temperature range of 300-400 °С [5][6][7][8]. In contrast, monolayer V 2 O 5 /TiO 2 catalysts demonstrate high activity and selectivity in the methanol oxidation to methyl formate and to dimethoxymethane at low temperatures (100-200 °С), whereas the formation of formaldehyde is greatly suppressed [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. On the other hand, all products mentioned above are of practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that methanol could be converted to dimethyl ether (DME) on acidic surfaces, to formaldehyde (FA) and methyl formate (MF) on oxidative surfaces, and to dimethoxymethane (DMM) on acidic and oxidative bifunctional surfaces [16]. In a previous work, the V 2 O 5 /TiO 2 modified with Ti(SO 4 ) 2 catalysts were proved to be effective for the selective oxidation of methanol to dimethoxymethane [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, upon calcination, MgO and Al2O3 were formed together with some copper-containing phases when the Cu content increased. As a remarkable feature, we could evidence the Mg atoms substitution by Cu atoms thanks to the observation of a rare "Fermi contact effect" considerably modifying the 27 Al NMR spectra. The Cu-doped solids exhibited a higher reactivity towards ethanol with improved dehydrogenation properties yielding acetaldehyde as a main product.…”
Section: Ethanol Conversion To Butanol and Highermentioning
confidence: 88%